Factors that contributing on the consumer preference of choosing hybrid cars: a case study of MBSA Automotive Sdn Bhd (Mercedes Benz Malacca) / Fatimah Syahirah Ramlee - Ramlee, Fatimah Syahirah (2017)
The purpose of this study is to determine the factors that contribute to the consumers preferences in choosing hybrid cars from Mercedes Benz. The study will examine the direct relationship between five criteria which is brand, price, car size and body style, self-image and efficiency with consumers' preference to purchase a hybrid car from Mercedes Benz. A survey of 80 respondents will be conducted at MBSA Automotive (Mercedes Benz) Sdn Bhd show room that located at Lot 17, Jalan Bendahara, Bandaraya Melaka. Standard multiple regression and Pearson correlation were used to test the hypotheses developed and research question. By having a better understanding of the consumers' preference to purchase a hybrid car, the automobile industry especially Mercedes Benz Company can make better marketing strategies and allocation of budget to attract consumer to purchase a hybrid cars.